Institutional Arrangements of the Political Party Wing on the Functions of Political Parties - Ibnu Sina Chandranegara; Syaiful Bakhri (Universitas Ahmad Dahlan, 2021)
Introduction to the Problem: In post-constitutional reform, every political party seeks to maximize each component within its party structure. One feature that has direct contact with the society is the political party wing, which is an essential resource in the regeneration of political party in internalizing its ideology and the development of the militancy character that can be done more efficiently. The institutional arrangements of the political party wing so far are still minimal. The limitations of the organizational structures of the political party wing have an impact on the uncertainty regarding the institutional organization of their wing organization.Objectives of the Study: This article identifies and examines the implication of the provision on the political party wing towards the institutional clarity of their wing organization; and the implications of the institutional arrangements of the political party wing on the functions of the political party.Methodology: This article uses normative legal research that analyses relevant secondary data related to the political party wing. This study concluded that the political party wing could be regulated as a public legal entity that is a part of the political party or an independent legal entity.Findings: This study indicates that the unclear provision regarding the political party wing is the potential to provide diverse interpretations by the political party in its institutional wing organization which is counterproductive or offers no meaning to the realization of the functions of the political party.Paper Type: Research Article